PROJECT-BASED LEARNING: MORAL ETHICS EDUCATION FOR THE COMMUNITY TO SUPPORT NATIONAL RESILIENCE IN EAST JAKARTA - Jaya Harjani, Haryanti; Sunarti, Herlina; Pujiastuti, Endang Tri; Heningtyas, Oryza Sativa; Erwin (Universitas PGRI Palembang, 2025)
The Community Service (PKM) program, themed